2017
DOI: 10.1590/1679-78253958
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Response and Microstructure Evolution of Oxygen-Free High-Conductivity Copper Liner in Explosively Formed Projectile

Abstract: The dynamic response and microstructure evolution of oxygen-free high-conductivity copper in a shaped charge liner are investigated through microstructural examination of a soft-recovery EFP. Adiabatic shear bands and voids which is the failure original of copper EFP can be observed in the rear part of the projectile. Numerical simulation results illustrate that the highest plastic strain reaches about 2.9 which can fully accommodate the grains deformation of copper EFP during the formation process at strain r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Dense Neumann bands consisting of deformation twins have been observed in an Fe EFP by Pappu et al [ 22 ]. The dynamic response and microstructural changes in a Cu EFP were investigated by Liu et al and the results showed that complete DRX occurred in the recovered projectile [ 23 ]. It shows that different microstructures will be generated during the EFP-forming process.…”
Section: Introductionmentioning
confidence: 99%
“…Dense Neumann bands consisting of deformation twins have been observed in an Fe EFP by Pappu et al [ 22 ]. The dynamic response and microstructural changes in a Cu EFP were investigated by Liu et al and the results showed that complete DRX occurred in the recovered projectile [ 23 ]. It shows that different microstructures will be generated during the EFP-forming process.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [21] found that the double-layer shaped charge was more conducive to increasing the tip velocity of the jet compared to the ordinary shaped charge. A new MEFP warhead was studied in [22] and tested the dispersion and penetration performance on five steel targets with different supports. In literature [23,24], a special evolvable warhead structure was proposed.…”
Section: Introductionmentioning
confidence: 99%
“…T2 copper which is commonly used in shaped charge liner [1][2][3][4] is an important nonferrous metal with superior plasticity. In shaped charge, T2 copper liner is crushed by detonation pressure and forms Jetting penetrator charge (JPC), metal Jet (JET) or explosively-formed projectile (EFP).…”
Section: Introductionmentioning
confidence: 99%